The Philippines a visual journey : welocme to the Philippines, an archipelago of enchanted islands - Reyes, Elizabeth V.; Davocol, Emil V.; Lucero, Patrick Nagaishi; Garbutt, Veronica (Tuttle Publishing, 2016)
This beautifully photographed travel pictorial captures the people, art, architecture, food and landscapes of the Philippines. The Philippine Archipelago with its 7,100 islands is culturally diverse and unique in Southeast Asia, and renowned for the splendor of its coastal beaches and terraced mountains. Seventy million Filipinos have been nurtured by both tropical environment and unique historical development through 300 years of Spanish Chistianization and 40 years of American modernization and have emerged as an attractive blend of East and West, soul and style. The island country is perhaps best known for the friendliness of its people and their natural sense of song, dance and hospitality. The archipelago is also called "Pearl of the Orient." With over 150 photographs and a detailed map, "Exciting Philippines" is an essential book for expats or tourists traveling to the Philippines."